Population structure of Gobiidae in a tropical urban estuary - Andrade, André Luiz Ramos Holanda de; Campos, Susmara Silva; Teixeira, Simone Ferreira (Journal of Environmental Analysis and Progress, 2020)
As spatiotemporal variations in estuaries affect the population structure of species, the study aimed to analyze the distribution of species of the family Gobiidae in the Capibaribe River's estuary city of Recife (northeastern Brazil). Sampling was performed bi-monthly from February 2009 to December 2012 at two sampling stations. The weight-length relationship of the species was determined using potential regression analysis. Density and biomass values were determined for each species per sampling station and season. The Mann-Whitney test was used to compare spatial and seasonal differences in abundance. A non-metric multidimensional scaling ordination was used to assess changes in species composition. Seven hundred eighty-eight individuals were caught. The most representative species of Gobiidae was Ctenogobius boleosoma, followed by Evorthodus lyricus and Gobionellus oceanicus. The relationship between total weight (TW) and standard length (SL) was potential and significant for both C. boleosoma (TW = 0.04SL2.1815) and E. lyricus (TW = 0.0272SL2.795), and both exhibited negative allometric growth. The analysis of the main species' spatial variation demonstrated a significant difference in the number of individuals for C. boleosoma (U = 528; p = 0.000005) and E. lyricus (U = 312; p = 0.000000). No significant difference in abundance was found between the dry and rainy season for either C. boleosoma (U = 1052.2; p = 0.4659) or E. lyricus (U = 1054; p = 0.4726). The two most abundant species have similar habits and customarily inhabit stressful environments. Ctenogobius boleosoma and E. lyricus are residents of the Capibaribe River's estuary, and both move to regions near the outfall of the river in the rainy season.